Penurunan Pada Eksistensi Penggunaan Bahasa Daerah Dalam Interaksi Generasi Masa Kini Berkenaan Dengan Literasi Kebudayaan - Tita Aulia; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
The decline in culture in the current generation is a form of the negative impact of the development of technology and digital media, basically a culture will continue to develop so that it can become a cultural adoption or produce a new culture, the same is true for language culture, especially in the use of regional languages in everyday life. In this case, Pancasila values need to be instilled in the current generation in order to increase the feeling of love for the country so that the presence of this technology does not erode the culture that existed before. This research on the cultural decline in using regional languages in the current generation as the identity of the Indonesian nation uses qualitative research with a type of literature study, so this research is based on previous research that has been carried out with similar studies.